2000
DOI: 10.1046/j.1365-2796.2000.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour ambulatory blood pressure in a population of elderly men

Abstract: Our results provide a basis for 24 h ambulatory blood pressure reference values in elderly men. The study confirms previous findings of a high prevalence of hypertension at older age. It also indicates that blood pressure is inadequately controlled in elderly treated hypertensives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…The threshold for elevated ambulatory daytime BP in this study (Ն135/85 mm Hg) has been proposed based on previous studies of ambulatory BP normality in different populations 15,31 and is also close to the daytime ambulatory BP (137/83 mm Hg) that by linear regression corresponded to an office BP of 140/90 in the present study population. 14 In conclusion, the present study in an elderly population showed for the first time that isolated ambulatory hypertension was a predictor of increased cardiovascular morbidity, independent of office BP and other established cardiovascular risk factors. The findings suggest that important prognostic information may be undetected when BP is measured only in the clinical setting.…”
Section: Discussionsupporting
confidence: 51%
“…The threshold for elevated ambulatory daytime BP in this study (Ն135/85 mm Hg) has been proposed based on previous studies of ambulatory BP normality in different populations 15,31 and is also close to the daytime ambulatory BP (137/83 mm Hg) that by linear regression corresponded to an office BP of 140/90 in the present study population. 14 In conclusion, the present study in an elderly population showed for the first time that isolated ambulatory hypertension was a predictor of increased cardiovascular morbidity, independent of office BP and other established cardiovascular risk factors. The findings suggest that important prognostic information may be undetected when BP is measured only in the clinical setting.…”
Section: Discussionsupporting
confidence: 51%
“…19 This limit is also close to the daytime pressure (137/83 mm Hg) that by linear regression analysis corresponded to an office BP of 140/90 mm Hg in the present study population. 18 A more restrictive definition (130/ 80 mm Hg) was used in a separate analysis to investigate the importance of the upper limit of normal ABP level, but it did not substantially change the results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Reading and data editing have been described in a previous study. 18 We defined white-coat hypertension as office BP Ն140/90 and daytime BP Ͻ135/85 mm Hg and sustained hypertension as office BP Ն140/90 and daytime BP Ն135/85 mm Hg. 19 The methods for anthropometric measurements and analysis of fasting serum triglycerides, cholesterol, and nonesterified fatty acids, as well as oral glucose tolerance test, have previously been described.…”
Section: Measurements At Age 70 Yearsmentioning
confidence: 99%
“…There seem to be only minor natural blood pressure alterations during this time in healthy elderly men. (Bjorklund et al, 2000) In patients suffering from OH the orthostatic reaction and its symptoms may be worse in the morning. (Mathias et al, 1999a;Mathias et al, 1999b) In this study 82% of the controls, 51% of the AD patients and 61% of the DLB patients had their orthostatic measurements carried out before noon.…”
Section: Discussionmentioning
confidence: 99%